Analisis modulus elastisitas daun pisang menggunakan video base labolatory (tracker) - Sabila Yasaroh; Heru Kuswanto (Universitas Pendidikan Ganesha, 2021)
Tempe packaging plays an important role to avoid contamination of microorganisms. Many studies have shown that the best packaging is banana leaves; compared to other wrappers such as plastic, paper and teak leaves. Of the various types of banana trees that grow in Indonesia, it is necessary to select the right leaves to produce an elastic wrapper so that it is not easily torn in order to support the optimization of tempe production itself. This research is an experimental study using linear regression analysis method, the relationship between the square of the oscillation period to the load mass and data collection for the determination of the modulus of elasticity of the material is carried out by using banana leaf oscillations with variations in the load mass which are videotaped and analyzed using tracker software. Furthermore, from the T2 to M data is carried out by linear regression and obtained a gradient value that will be used to determine the modulus of elasticity of banana leaves. It was obtained that the modulus of elasticity of banana leaves was E = 4.92 × 102 Nm-2 for young leaves, E = 8.59 × 102 Nm-2 for medium leaves, and E = 13.22 × 102 Nm-2 for old leaves with relative error of 11.6% or 0.116.